Early enteral nutrition combined with supplemental parenteral nutrition vs. total parenteral nutrition after pancreaticoduodenectomy: a retrospective and propensity score-matched analysis of postoperative complications - Li, Jialing; Hu, Defu; Sheng, Jianjie; Wang, Zhiang; Hang, Hexing; Qiu, Yudong; Chen, Dayu; Fu, Xu (Frontiers in Nutrition, 2025)
BackgroundPostoperative nutritional support strategy after pancreaticoduodenectomy (PD) remains controversial. This retrospective study aims to evaluate early enteral nutrition (EEN) combined with supplemental parenteral nutrition (SPN) vs. parenteral nutrition (PN) as postoperative nutritional support, focusing on early clinical outcomes and postoperative complications in patients who underwent PD.MethodsClinical data from consecutive patients who underwent PD between January 2022 and July 2024 were collected and analyzed in this retrospective study. The primary outcome was the incidence of postoperative complications. The secondary outcomes included specific postoperative complications, such as delayed gastric emptying (DGE), bile leak (BL), chyle leak (CL), acute pancreatitis (AP), postpancreatectomy hemorrhage (PPH), and infectious complications, compared between the two groups. A propensity score-matched (PSM) analysis was performed to balance baseline confounders between the groups.ResultsAccording to perioperative nutritional protocols, 248 patients were included and divided into the EEN + SPN group (n = 116) and the PN group (n = 132). After PSM, baseline characteristics were balanced between the EEN + SPN group (n = 59) and the PN group (n = 59). No statistically significant differences were observed in the incidence of complications between the two groups, either before or after PSM (all p > 0.05). Before PSM, the overall incidence of severe postoperative complications was 10.1%. The EEN + SPN group demonstrated a significantly lower incidence of severe complications compared to the PN group both before and after PSM (p < 0.05). Analysis of secondary outcomes (which included a comparative analysis of detailed complications) revealed no significant differences between the groups.ConclusionIn conclusion, this study demonstrates that for patients at nutritional risk following PD, EEN + SPN is a safe and feasible nutritional support strategy and is associated with a significant reduction in the incidence of severe complications.